Rollercoaster loop shapes - Pendrill, Ann Marie ; 0000-0002-1405-6561 (Physics Education, 2005)
Many modern rollercoasters feature loops. Although textbook loops are often circular, real rollercoaster loops are not. In this paper, we look into the mathematical description of various possible loop shapes, as well as their riding properties. We also discuss how a study of loop shapes can be used in physics education.